Hardcore smoking among daily smokers in male and female adults in 27 countries: a secondary data analysis of Global Adult Tobacco Surveys (2008-2014). (2018) - Sreeramareddy, Chandrashekhar T; Hon, Joanne; , Anshad Mohamed Abdulla; Harper, Sam
No abstract available